2019
DOI: 10.3892/ol.2019.10936
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis of Ewing's sarcoma: Seeking key candidate genes and pathways

Abstract: Ewing's sarcoma (ES) is the second most common bone tumor among children and adolescents worldwide. However, the genes and signaling pathways involved in ES tumorigenesis and progression remain unclear. The present study used two gene-expression profile datasets (GSE17674 and GSE31215) to elucidate key potential candidate genes and pathways in ES. Differentially expressed genes (DEGs) were identified and a functional enrichment analysis was performed. A protein-protein interaction (PPI) network was constructed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Besides, ISG15 has been described to play a pro-tumoral role in various malignancies like bladder, nasopharyngeal, breast, hepatocellular or pancreatic cancer [18-24, 27-30, 44]. In sarcoma, a recent bioinformatics study into Ewing sarcoma, comparing tumour samples versus non-cancerous samples, identified ISG15 as one of the hub genes in a protein-protein interaction network (PPI) [45]. Conversely, ISG15 showed a protective anti-tumour role in glioblastoma and ovarian models [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, ISG15 has been described to play a pro-tumoral role in various malignancies like bladder, nasopharyngeal, breast, hepatocellular or pancreatic cancer [18-24, 27-30, 44]. In sarcoma, a recent bioinformatics study into Ewing sarcoma, comparing tumour samples versus non-cancerous samples, identified ISG15 as one of the hub genes in a protein-protein interaction network (PPI) [45]. Conversely, ISG15 showed a protective anti-tumour role in glioblastoma and ovarian models [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, numerous researches have been published on many different cancer types. Similarly, ES is no exception, some key genes involved in metastasis and development [5][6][7][8]. However, these studies contain one or two datasets.…”
Section: Introductionmentioning
confidence: 99%